Alternative Risk Metrics to Evaluate Tradeoffs between Efficiency and Equity of Risk Reduction - Johnson, David; ICASP14; Geldner, Nathan (My University, 2023)
A common criticism of traditional benefit-cost analysis (BCA) is that benefit-cost ratios (BCRs) are reductive, in the sense that they aggregate all benefits and costs into a scalar value; decision rules that aim to maximize BCRs ignore distributional impacts in favor of pure economic efficiency. In the context of flood risk management, all else equal, benefit-cost analysis favors protection of affluent communities comprised of assets with higher replacement costs. Allocations of scarce resources for flood protection based on BCA could therefore lead to inequitable provisions of risk reduction. This paper analyzes ranked preferences for flood protection projects included in Louisianaﾒs Comprehensive Master Plan for a Sustainable Coast, a 50-year, $50 billion USD suite of infrastructure investments primarily targeting risk reduction and coastal restoration. In addition to BCRs, we also estimate cost effectiveness measures such as the reduction, per unit of project cost, in the expected number of residential structures inundated over the planning horizon. Measures like this intentionally ignore the replacement costs of structural assets, implicitly valuing protection of each household equally regardless of wealth. In a sense, we consider how preferences vary, depending on whether decision makersﾒ preferences are to protect wealth or to protect households. We then overlay census data to estimate the risk reduction which would be afforded across different demographic categories by project portfolios of varying budgets, examining differential outcomes across income, race, and urbanicity. Our analysis suggests that the choice of metric has a substantial impact on the rank-ordered preferences for flood protection projects, and that dramatic increases in equity can be obtained by placing only a small weight on metrics that are wealth-agnostic. In our experience, decision makers often want to incorporate equity and social vulnerability considerations into their planning processes, but they either do not know how or they worry about pushback if plans appear to explicitly favor one group over another. By incorporating alternative risk metrics into a cost effectiveness analysis of flood protection projects, our results indicate that more equitable outcomes can be achieved without explicitly optimizing for it and with minimal loss in economic efficiency.
14th International Conference on Applications of Statistics and Probability in Civil Engineering(ICASP14)
PUBLISHED